2009
DOI: 10.1007/s10529-009-9924-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of living Salmonella cells using bioluminescence

Abstract: ATP-based bioluminescence using mutant firefly luciferase was combined with an immunochromatographic lateral flow test strip assay for Salmonella enteritidis detection. In this combination method, the Salmonella-antibody-gold complex captured at the test line on the test strip was lysed by heat-treatment, and the ATP released from the cells was measured using mutant luciferase. This method resulted in approximately 1,000 times higher sensitivity in the detection of Salmonella (i.e. 10(3) c.f.u./ml) compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We previously developed the higher catalytic mutant luciferase FM (Fujii et al 2007) and applied this enzyme for e cient assays for ATP as well as D-luciferin-generating enzymes using peptide-modi ed luciferin (Noda et al 2010;Noda et al 2008;Urata et al 2009). Here we found that luciferase CR showed higher luminescence than FM within various ATP concentrations in the presence of sodium chloride (Fig.…”
Section: Atp Assay Using Luciferase Crmentioning
confidence: 99%
“…We previously developed the higher catalytic mutant luciferase FM (Fujii et al 2007) and applied this enzyme for e cient assays for ATP as well as D-luciferin-generating enzymes using peptide-modi ed luciferin (Noda et al 2010;Noda et al 2008;Urata et al 2009). Here we found that luciferase CR showed higher luminescence than FM within various ATP concentrations in the presence of sodium chloride (Fig.…”
Section: Atp Assay Using Luciferase Crmentioning
confidence: 99%
“…Lateral flow immunoassay (LFI) is a rapid, simple, and cost-effective method that has attracted growing interest from researchers and has been successfully used to detect pathogens (Urata et al, 2009;Ching et al, 2012;Xie et al, 2014;Chen et al, 2015a), toxins (Wang et al, 2011;Chen et al, 2013a;Ren et al, 2014), veterinary drugs (Song et al, 2013;Romero et al, 2014;Samsonova et al, 2015), heavy metals (Cho and Irudayaraj, 2013), and pesticides (Hossain et al, 2009;Shaker and Elsharkawy, 2015) in milk and milk powder. This review aims to describe recent developments in LFI for the detection of hazardous substances in milk and milk powder.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed to detect S. enterica; these methods include polymerase chain reaction (PCR) (Hein, Flekna, Krassnig, & Wagner, 2006;Perelle et al, 2004;Riyaz-Ul-Hassan, Verma, & Qazi, 2013), enzyme-linked immunosorbent assay (ELISA) (Durant, Young, Nisbet, Stanker, & Ricke, 1997;Galikowska et al, 2011;Mansfield & Forsythe, 2000), gold lateral flow strip (GLFS) (Urata, Iwata, Noda, Murakami, & Kuroda, 2009), and surface plasmon resonance (SPR) (Son, Kim, Kothapalli, Morgan, & Ess, 2007). PCR is highly sensitive, but it requires precise and expensive instruments.…”
Section: Introductionmentioning
confidence: 99%